2002
DOI: 10.4141/a01-061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delaying the LH surge and altering LH secretion on plasma hormones and embryo production in heifers superstimulated with FSH

Abstract: . 2002. Effects of delaying the LH surge and altering LH secretion on plasma hormones and embryo production in heifers superstimulated with FSH. Can. J. Anim. Sci. 82: 357-366. Ovarian follicles were ablated by ultrasound-guided transvaginal aspiration in 20 Holstein heifers allocated to four groups (n = 5 per group). The first group (SOV) was superstimulated conventionally with FSH. In the other superstimulated groups, the LH surge was delayed by 24 h with progesterone (CIDR) and 100-µg injection of GnRH. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Earlier studies have found that a delay in LH surge of 11.4 h in heifers [28] and 24-48 h in mice [29,30] reduces fertilization and implantation rates and increases embryonic death and chromosome abnormalities [28][29][30]. In superovulation models of cattle, a delayed surge of 24-48 h was found to be associated with compromised follicular development [31], decreased ovulation rate, and lowered rate of embryo production [32]. It is unclear if a short delay of 3 h, such as that seen in this study, would have physiological impact on oocyte quality.…”
Section: Consequences Of Delayed Lh Surgementioning
confidence: 99%
“…Earlier studies have found that a delay in LH surge of 11.4 h in heifers [28] and 24-48 h in mice [29,30] reduces fertilization and implantation rates and increases embryonic death and chromosome abnormalities [28][29][30]. In superovulation models of cattle, a delayed surge of 24-48 h was found to be associated with compromised follicular development [31], decreased ovulation rate, and lowered rate of embryo production [32]. It is unclear if a short delay of 3 h, such as that seen in this study, would have physiological impact on oocyte quality.…”
Section: Consequences Of Delayed Lh Surgementioning
confidence: 99%